Supply Chain Risk Management Assessment and Strategy: Case Study in a Hospital Pharmacy - Mushonnifun Faiz Sugihartanto; Muhammad Rizaldy Mahendra; Imam Baihaqi; Hanif Rizaldy (Jurnal Teknologi dan Manajemen, 2024)
Health service providers such as hospitals have a very diverse supply chain in quantity and type, one of which is medicine. Hospital Pharmacy Installation (IFRS) is one of the health support activity units responsible for planning, procurement, management, storage, distribution, use of drugs, equipment, and pharmaceutical services for medical devices related to the distribution of drugs used in hospitals. Pharmacy has several risks that need to be addressed to increase customer satisfaction. This study aims to determine the extent of the implementation of Supply Chain Risk Management, identify risks in supply chain activities, and obtain risk management strategies. In this study, the method used is the assessment of Supply Chain Risk Management and continued the evaluation of the drug chain in pharmaceutical installations with the House of Risk. It is divided into two stages, namely House of Risk Stage 1, which is used to decide the risk in each supply chain, and House of Risk Stage 2, to offers a decision-making strategy for each chosen decision. There are 20 risk events and 20 risk agents in the House of Risk stage 1, and 11 proposed risk management strategies in the House of Risk stage 2. Out of 20 risks identified in stage 1, 11 risks contributed to 80% highest risk, and the top three are drug shortage, inappropriate planning, and unclear doctor’s writing. In stage 2, the three most prioritized strategies are e-prescription implementation, clear signs for LASA drugs, and conducting supplier performance evaluation.